Canine dermatomyositis: A case report - PAPADOGIANNAKIS (E. Ι. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ) E. I.; KONTOS (Β. Ι. ΚΟΝΤΟΣ) V. I.; TONTIS (Δ. ΤΟΝΤΗΣ) D. (Journal of the Hellenic Veterinary Medical Society, 2017)
This article describes a case of canine dermatomyositis in a German shepherd cross. The dog exhibited skin lesions on the ear pinnae, legs, face and the tail, along with mastication difficulty and atrophy of the temporal and masticatory muscles. Histopathological lesions of the skin were characterized by vacuolar degeneration of basal cells, dermoepidermal clefts and vasculitis, while the respective lesions of masticatory muscles by inflammation, phagocytosis and disruption of muscle fibers. Vitamin E and pentoxyphylline administration was unsuccessful.